2014
DOI: 10.1111/ejn.12755
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in the resting‐state motor networks influences the kinematic processes during motor sequence learning

Abstract: Neuroimaging studies support the involvement of the cerebello-cortical and striato-cortical motor loops in motor sequence learning. Here, we investigated whether the gain of motor sequence learning could depend on a priori resting-state functional connectivity (rsFC) between motor areas and structures belonging to these circuits. Fourteen healthy subjects underwent a resting-state fMRI session. Afterward, they were asked to reproduce a verbally-learned sequence of finger opposition movements as fast and accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 51 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…individuals learning the most experienced the largest reduction in cerebellar inhibitory output ( Jayaram et al, 2011 ). Bonzano and colleagues (2015) recently showed that greater (motor) cortico-cerebellar connectivity (i.e. less inhibition) was correlated with learning on a finger-tapping task in PwMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…individuals learning the most experienced the largest reduction in cerebellar inhibitory output ( Jayaram et al, 2011 ). Bonzano and colleagues (2015) recently showed that greater (motor) cortico-cerebellar connectivity (i.e. less inhibition) was correlated with learning on a finger-tapping task in PwMS.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of functional brain alterations on disease progression, motor deficits, and overall quality of life in clinical populations is a topic of great interest. Mounting evidence reveals that reduced structural connectivity and functional neural connectivity are related to movement deficits in PwMS ( Bonzano et al, 2008 ; Bonzano et al, 2015 ; Fling et al, 2014b ; Petsas et al, 2014 ). Several studies report altered functional connectivity of the motor network in PwMS ( Janssen et al, 2013 ; Lowe et al, 2002 ), however; little is known about how these differences in functional communication contribute to lower limb dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in resting-state functional connectivity between M1 and cerebellum with motor learning has also been reported in humans. For instance, participants with greater motor sequence learning rate increases have stronger functional connectivity of the M1 and SMA with the cerebellum 35 . Increases in strength in the fronto-parietal network and the cerebellum network after 11 minutes of motor learning have also been detected 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, paleocerebellum can adjust the activity of anti-gravity muscles to provide adequate strength of muscle tension that is needed to maintain balance while standing and movements. Research (Bonzano et al, 2014) indicated that important functional connections including cerebellum responsible for motor learning improvement, and cerebellum related to the hemisphere directly controlling the finger movements. The relevant results (Iglói et al, 2014) stepped on to emphasize the remarkable role of cerebellum in both motor and cognitive function.…”
Section: Discussionmentioning
confidence: 99%